KH Mohammad Cholil Bisri's Da’wah in the Field of Islamic Politics in Indonesia - Riyadi, Agus; Karim, Abdul; Hakim, Lukmanul (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2024)
This study aims to analyze the political da’wah activities of KH Mohammad Cholil Bisri in Indonesia and its impact on the development of Islamic politics. Using descriptive qualitative methods and political approaches. Data collection techniques through interviews and documentation. The study results indicate that KH Cholil Bisri plays an important role in Islamic politics in Indonesia, especially through preaching that integrates Islamic values with national life. Since the 1971 to 1992 elections, he has been active in voicing the importance of Islamic morality in politics while overseeing the birth of the National Awakening Party (PKB). His political da’wah paved the way for inclusive and moderate Islam in national politics. The impact of KH Cholil Bisri's political da’wah is the creation of a strengthening of moderate Islamic politics by Indonesian national values, making him an important figure in formulating fair and just state policies. The implications of this study suggest that KH Mohammad Cholil Bisri's political da’wah significantly contributed to the shaping of inclusive and moderate Islamic politics in Indonesia, offering valuable insights for future political leaders in integrating Islamic values with national governance to promote justice, unity, and social harmony.